Caspase-7 in molar tooth development - Matalova, E; Vanden Berghe, T; Svandova, E; Vandenabeele, P; Healy, C; Sharpe, P T; Tucker, A S (Archives of oral biology, 2012)
OBJECTIVES: The primary enamel knot (PEK) is a population of cells that shows spatio-temporal restricted apoptosis during tooth development. It has been shown that caspase-9 and Apaf-1 are essential for apoptosis in the PEK as well as the central caspase-3. Caspase-7, as another executioner member in the caspase machinery, is considered to have caspase-3 like properties. DESIGN: The aim of this study was to detect caspase-7 activation during molar tooth development with a special focus on the cells of the PEK and to correlate the expression with the pattern of apoptosis and caspase-3 activation. Apoptosis in the PEK was investigated in caspase-7 deficient mice to examine the functional consequence of loss of this specific caspase. In addition, odontoblasts and ameloblasts, which are known to undergo cell death during their secretory and maturation stages, were investigated. RESULTS: Cleaved caspase-7 was found in the apoptotic region of the PEK, however, caspase-7-deficient mice still possessed apoptotic cells in the PEK in a similar distribution to the wild type. Caspase-7 is therefore not essential for apoptosis in the PEK. Notably, cleaved caspase-7-positive cells were found at later stages in odontoblasts and ameloblasts, but expression did not correlate with apoptosis in these tissues. CONCLUSIONS: The results indicate a non-essential apoptotic role of caspase-7 in the PEK apoptosis but suggest also possible non-apoptotic functions for caspase-7 in tooth development.
Keywords: Odontoblasts; apoptóza; Molar; Ameloblasts; vývojová regulace genové exprese; Tomography, X-Ray Computed; myši inbrední C57BL; odontogeneze; Mice; moláry; kaspasa 7; Gene Expression Regulation, Developmental; odontoblasty; zvířata; ameloblasty; Caspase 7; koncové značení zlomů DNA in situ; myši; In Situ Nick-End Labeling; Odontogenesis; počítačová rentgenová tomografie; Mice, Inbred C57BL; Apoptosis; Animals